Emerging mechanisms progress of colorectal cancer liver metastasis - Zhao, Wenhu; Dai, Shipeng; Yue, Lei; Xu, Fan; Gu, Jian; Dai, Xinzheng; Qian, Xiaofeng (Frontiers in Endocrinology, 2022)
Colorectal cancer (CRC) is the third most common malignancy and the second most common cause of cancer-related mortality worldwide. A total of 20% of CRC patients present with distant metastases. Hepatic portal venous system, responsible for collecting the majority of intestinal blood, makes liver the most common site of CRC metastasis. The formation of liver metastases from colorectal cancer is a long and complex process. It involves the maintenance of primary tumor, vasculature invasion, distant colonization and metastasis formation. In this review, we serve on how the CRC cells acquire stemness, invade in the vascular, and finally colonize in the liver. In addition, we highlight how the resident cells of liver and immune cells interact with CRC cells. We also discuss the current immunotherapy approaches and challenges we faced, and finally look forward to finding new therapeutic targets based on novel sequencing technologies